Design of Water Level Control in Tank Based on Fuzzy Logic - Ilmi Rizki Imaduddin (Universitas Ahmad Dahlan, 2020)
Liquid level control is a regulatory system that is widely used by the petrochemical industry, paper mills, and steam power plants (PLTU). Fuzzy control techniques have light computing capabilities and do not require knowledge of the parameters of the system. The purpose of this research is to design and design a device that can make it easier to adjust the liquid level in the storage tank and observe the fuzzy control performance. Control is done by adjusting the valve opening in the storage tank. From the results of this study, data on setpoint 56 is obtained, the valve is at an angle with all open status (BS), at the first second or 1 second, and at set point 41, the valve is at an angle with a half-closed status (SN), in the 13th second, and the valve will be closed all (NS), if the valve is at an angle at the set point 29, with a time of 1620 seconds or 27 minutes. Based on this research, the proposed system is able to control the water level in the tank using fuzzy control.